MENINGKATKAN KARAKTER SOPAN SANTUN MELALUI PERMAINAN ULAR TANGGA AKHLAKUL KARIMAH UNTUK ANAK KELOMPOK B DI RAUDHATUL ATHFAL (RA) DARUL MAKMUR TEGALDLIMO BANYUWANGI - Moh. Anas Syamsudin; Yayuk Habibah Rosadi (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Teaching manners to early childhood is very important. In Indonesian government regulations, the character of manners for early childhood has been contained in the form of indicators that must be mastered by children at a certain age. But unfortunately there are several indicators of polite character that have not been mastered by group B children in RA Darul Makmur, namely 1.) Children are not used to shaking hands with teachers or friends, 2.) Children like to swear, 3.) The child likes to mock his friends, 4.) The child is not used to saying please, sorry and thank you, 5.) Children are not used to asking permission when borrowing 6.) The child likes to interrupt the teacher's whispering. The purpose of this study was to determine the application of playing akhlakul karimah snakes and ladder to improve the character of manners in group B children in RA Darul Makmur, as well as to determine the improvement of children's character manners after the implementation of the game. The type of research used is classroom action research. Data collection techniques use observation, documentation, and treatment. Data analysis techniques use descriptive qualitative and descriptive quantitative. The subjects in this study were group B children totaling 14 children. The results of this study show that the application of the snake and ladder game akhlakul karimah for grade B children in RA Darul Makmur is carried out in four stages, namely 1.) preparation, 2.) implementation, 3.) evaluation, 4.) observation of changes in children's behavior. Through the application of the snake and ladder game akhlakul karimah, the character of the manners of group B children in RA Darul Makmur has improved. This can be seen from the number of children who achieved completion in the pre-cycle stage as many as 5 children (35.71%), cycle 1 as many as 8 children (57.14%), and cycle 2 as many as 12 children (85.71%).